Post-producing the modern – Guidelines for an energy development as an architectural transition - Giuseppe Marsala; Giulia Renda (Agathón)
The city of Modern legacy and 20th-century built architecture are the fields of investigation for the architectural design’s statutes updating in the light of climate change and ecological transition; the energy transition theme, therefore, becomes an opportunity for a reflection on the fundamentals of design and its operational procedures for a necessary energy transition, which is capable of interpreting the new challenges of our ecosystem. From this perspective, the essay retraces contemporary architectural experiments in an energetic key performed on the structure of modern architecture, starting from the re-interpretation of its theoretical principles.